Nuclear Security Education and Training in Pakistan - Noreen Iftakhar; Sitara Noor (International Journal of Nuclear Security, 2017)
The world’s growing dependence on nuclear power as a reliable and clean source of energy demands equal safety and security considerations. The security challenges associated with nuclear materials, facilities, and technologies are emerging at an alarming rate, necessitating corresponding counter measures. Pakistan has invested significant resources in nuclear security education and training to meet the requirements of its expanding nuclear program. For example, Pakistan’s Center of Excellence for Nuclear Security is responding to the growing demands of this crucial area and imparting education and training in various sub-domains of nuclear security. Pakistan’s focus on nuclear security education and training has led to the development of a program that has received international acclaim, and has made significant contributions toward worldwide nuclear security.
Keywords: nuclear security; education; training; CoE; PCENS